Veganism and its Contribution to a Sustainable Future - sandhu, suchi (2020)
The deteriorating fate of the environment appears in the form of climate change, resource depletion, air, and water pollution. Overconsumption is a contributor to these environmental issues since the increase in the production of food causes greenhouse gas emissions and depletion of natural resources. The need for change is empirical and a vegan lifestyle can be a possible solution to accomplish sustainability.